Gamified Diagnostic Assessment Using Quizizz: Investigating Motivation and Perceptions of Indonesian ESL Students - Sholihah, Laili Inayatus; Miranty, Delsa (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This study explores the impact of Quizizz as a diagnostic assessment platform on the motivation and perceptions of third-grade students at SMPN 3 Tigaraksa in their English lessons. A quantitative research design was employed, using a questionnaire distributed to 35 students, with results analyzed through descriptive statistics. The ages of the samples in this research are between 14 and 15 years old. The questionnaire utilized a four-point Likert Scale based on their agreement and disagreement. This questionnaire was distributed through Google Forms. The studyâ€™s findings revealed that using Quizizz increased students’ intrinsic motivation and positive perceptions of learning English. The students found learning English to be more enjoyable and engaging. The competitive and engaging use of Quizizz resulted in greater interest and confidence in English language learning. Related to the limitation of this research is that it focuses solely on Indonesian ESL students, which may restrict the generalizability of the findings to learners in other cultural or linguistic contexts. This study offers insightful information for teachers to use technology-integrated learning methods, such as Quizizz, as a diagnostic assessment platform. It can motivate and help teachers design more effective teaching strategies according to ESL students’ needs in learning English.